FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN KELOMPOK TANI TERNAK SAPI DI DESA PENYESAWAN KECAMATAN KAMPAR (Studi Kasus Kelompok Tani Bukik Batang Potai) - Try Wahyuni; Rita Yani Iyan; Mardiana ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to know the factors that affect the income of live stock farmers group Bukik Potai Stems in the village of Penyesawan sub-district of Kampar as well as to know what factors affect the income of the farmers group dominant cattle BukikPotai Stems in the village of Penyesawan subdistrict of Kampar. Sampling method used is the method of sampling of saturated (census), where the total population of 24 members of the group are examined. Methods used in research is descriptive quantitative methods and the quantitative analysis the analysis simultaneously test ( f) , and partial test ( t ) with program assistance spss 16 .Data-data used in research is the capital , the number of cattle respondents and the experience raise the farmers cattle bukik stem potai in the village penyesawan in kampar. The research results show that value adjusted r square of 0,859 which means that 85.9 % gain group cattle farmers in stir in together by variable in the mode.While the rest 14.1 % in stir by other factors outside model .In partial variable the number of capital ( x1 ) , total number of livestock ( x2 ) , and experience animal farmers ( x3 ) influential in significant impact on variable dependent namely the farmers to bukik stems potai ( y ).KeyWord : Income , capital, and experience farmers